Torrefied Cogon grass effects of torrefaction process parameters on fuel properties of solid and condensate products - Palanca, Alvin G.
Torrefaction is a thermal pretreatment process of producing solid fuel by heating biomass below 300°C under anoxic condition. This pretreatment process improves the fuel characteristics of Cogon grass and its energy density were comparable to that of a subbituminous class B and C coals. Sun-dried Cogon grass were torrefied in a fabricated batch torrefaction reactor and their solid and organic condensate products were analyzed. A response surface methodology is used to examine the effects of torrefaction reaction temperature, feed size, reaction time, and Cogon grass parts on energy density, mass yield, and energy yield of the solid products as well as the effects of reaction temperature and reaction time on energy density and mass yield of the organic condensate. Mass yield decreases as reaction temperature is increased and increases as feed shift from leaves to nodes, from 54% at 250°C to 43% at 285°C and 39% using leaves to 60% using nodes. Also energy yield increase from 50% to 82% as feed shift from leaves to nodes. This is however compensated by an increase of 34 % on its energy density. In addition, energy density of the condensed gas products can be predicted using the four process parameters as an input variable on the surface response model for energy density of condensed organic volatiles.